Solving (a+1)(a+2) = 0 by Factoring
This equation is already in factored form, making it simple to solve. Here's how:
The Zero Product Property
The Zero Product Property states that if the product of two or more factors is zero, then at least one of the factors must be zero.
Solving the Equation

Identify the factors: We have two factors: (a+1) and (a+2).

Apply the Zero Product Property: Set each factor equal to zero:
 a + 1 = 0
 a + 2 = 0

Solve for 'a':
 a = 1
 a = 2
Solution
Therefore, the solutions to the equation (a+1)(a+2) = 0 are a = 1 and a = 2.
Verification
We can verify these solutions by plugging them back into the original equation:
 For a = 1: (1 + 1)(1 + 2) = (0)(1) = 0
 For a = 2: (2 + 1)(2 + 2) = (1)(0) = 0
Both solutions satisfy the original equation, confirming their validity.